The Current Health Belief of Exercise Conditions of Chinese College Students and Ways of Improvements: An Analysis Based on the Health Belief Model - Gong, Lamei; Sheng, Jiazhi (Frontiers in Psychology, 2022)
This study aimed to discuss the differences in the parameters of exercise health beliefs among college students of different genders, assess the relationship between demographic factors and parameters of exercise health beliefs, and examine the relationship between exercise self-efficacy and internal components of exercise health beliefs. A total of 313 Chinese college students from the Sichuan University of Arts and Science completed the exercise health belief scale voluntarily under the explanation by the tutor. The results showed that compared with female students, male students have higher perceived benefits and self-efficacy of exercise and lower perceived barriers. Monthly family income has a significant positive correlation with self-efficacy of exercise, and it has a significant negative correlation with perceived subjective barriers to exercise disorder. The self-efficacy of exercise has a significant positive correlation with perceived benefits and perceived severity, and it has a significant negative correlation with perceived subjective barriers and perceived objective barriers. From the structural equation model, we found that family income no longer had a significant impact on the self-efficacy of exercise. Within the exercise health belief constituent items, we found only that subjective perceived barriers were significantly negatively correlated with self-efficacy for exercise. According to the study, our findings provide a new psychological angle for understanding the exercise condition of college students and the restraining factors and provide new insights into increasing the self-efficacy of exercise to lower the subjective barriers to exercise. Future studies will focus on the relationship between exercise health belief components and physical activity levels and exercise behaviors of college students.